Serat Wulangreh: Ajaran Keutamaan Moral Membangun Pribadi yang Luhur - Sri Yulita Pramulia Panani (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2019)
This research explored the content of the teachings of moral virtue within the Serat Wulang Reh. It was aimed to describe the teachings of moral virtue which can shape current generation of the nation in establishing noble personality and strengthen moral characters amidst modernity. This study was bibliographical research based on the philosophical research model of factual historic queries concerning texts. In the process of analyzing research data, researchers used methodical elements namely, interpretation, idealism, comparison, and description. The results described how to be a noble person according to Serat Wulang Reh. First, one must realize the purpose and meaning of life as human and creature of God. The teachings of moral virtue in 'Serat Wulang Reh' outlined the teachings of being religious, e.g. worshiping in five devotions, practicing worships, always remembering God and controlling the carnal desire with care and concern. The teachings of other virtues included developing moral attitudes in family circle, in society and relationship to the state. In conclusion, the harmony of life, salvation of the world and hereafter can be achieved through the implementation of the whole teachings described in Serat Wulang Reh.